Received signal strength localization with an unknown path loss exponent - Chan, Y. T.; Lee, B. H.; Inkol, R.; Chan, F. (2011 24th Canadian Conference on Electrical and Computer Engineering(CCECE), 2011)
Received Signal Strength (RSS) measurements obtained at locations in the vicinity of an emitter can be used to estimate the emitter location given a suitable path loss model. For commonly used propagation models, the RSS has a dependence on the emitter to sensor separation, d, of the form P ∝ d -α , where the path loss exponent, α, is typically between 2 and 4 depending on the terrain. This uncertainty is a problem since a solution for the emitter location obtained using a suboptimal choice of α will suffer from degraded accuracy. To resolve this issue, a near maximum likelihood (ML) estimator for both α and emitter position (x,y) has been developed. By expressing (x,y) in terms of α and substituting the results into the ML-function, the 3-D minimization problem is simplified to 1-D. A simple search in α then gives the (α,x,y) estimates. Simulation experiments corroborate the proposed approach and demonstrate estimation accuracy close to the Cramer-Rao Lower Bound.